The Study on The Seed Storability of Black Soybean (Glycine max L. Merrill) Intercropped with Sweet Sorghum (Sorghum bicolor L. Moench) - Purwanti, Setyastuti; Immawati, Dhika Rizky; Prajitno, Djoko (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2018)
The experiment was aimed to know how to maintain seed quality during storage by planting black soybean and sweet sorghum in row using an intercropping system. This experiment was conducted in the Laboratory of Seed Technology, Faculty of Agriculture, Gadjah Mada University, Yogyakarta, Indonesia, from November 2013 until April 2014. This experiment was single factor experiment arranged in CRD (Completely Randomized Design) with four treatments and four replications. The treatments consisted of monoculture of black soybean, intercropping between black soybean and sweet sorghum with various row ratios, i.e. 3:1, 4:1, and 6:1. The seeds were stored as many as 250 g for each treatment in hermetic plastic at normal temperature (27-28 ºC) for five months. Seed quality testing was performed every month. Data collected included moisture content, germination, vigor index and vigor hypotetical of the seeds. The result of this experiment showed that the quality of black soybean seeds yielded from intercropping with sweet sorghum gave the same effect compared to the black soy bean seeds yielded from monoculture. Seed quality of black soybean planted in intercropping and monoculture system could be well maintained until the fourth months of storage.